PRINTING DEVICE AND PRINTING METHOD - TOKUDA, Yusuke (2024)
A printing device includes a printer including a printing head to print a printing subject on a printing medium; a transporter including a roller to, while pressing the printing medium against the printing head, transport the printing medium in a feeding direction and a retracting direction; and a presser to, when the printing medium is transported in a feeding direction, cause the roller to press the printing medium against the printing head with first pressure and, when the printing medium is transported in a retracting direction, cause the roller to press the printing medium against the printing head with second pressure different from the first pressure.